Pneumocephalus Associated with Cerebrospinal Fluid Fistula as a Complication of Spinal Surgery: A Case Report - Ken Sasaki; Tomoyuki Matsumoto; Toshiyuki Mizuno; Shinichi Ikuta; Toshihiro Akisue; Hiroyuki Fujioka; Minoru Doita; Masahiro Kurosaka; Ryosuke Kuroda (Case Reports in Medicine)
Pneumocephalus is a well-known condition following head trauma, but is rare as an injury or as a result of surgery of the spine. We present a 76-year-old patient with a rare case of pneumocephalus associated with a cerebrospinal fluid fistula as a complication of surgical treatment for cervical myelopathy. Although cerebrospinal fluid leakage was noted and the injured dura was carefully sutured at operation, tension pneumocephalus occurred. The resultant pneumocephalus was diagnosed based on neurogenic symptoms including sudden convulsion, head radiograph, and computed tomography scan. The benign course of the pneumocephalus postdiagnosis did not require secondary operation.